Effect of Polypropylene Modification by Impregnation with Oil on Its Wear and Friction Coefficient at Variable Load and Various Friction Rates - Paweł Sędłak; Beata Białobrzeska; Tomasz Stawicki; Piotr Kostencki (International Journal of Polymer Science)
Laboratorial two-body wear testing was carried out in order to assess effects of polypropylene modification by impregnating it with oils on friction coefficient and wear in comparison to those parameters of unmodified polypropylene, Teflon, and polyamide during operation under conditions of sliding friction without lubrication. Wear behaviour of the tested specimens was investigated using ASTM G77-98 standard wear test equipment. Recording program made it possible to visualise and record the following parameters: rotational speed and load, linear wear, friction coefficient, temperature of the specimen, and ambient temperature. In addition, wear mechanisms of the analysed materials were determined with use of scanning electron microscopy. In the case of the remaining tested polymers, the most important mechanism of wear was adhesion (PP, PTFE, PA 6.6, and PA MoS2), microcutting (PTFE, PA 6.6, and PA MoS2), fatigue wear (PTFE), forming “roll-shaped particles” combined with plastic deformation (PA 6.6 and PA MoS2), and thermal wear (PP). Impregnation of polypropylene with engine oil, gear oil, or RME results in significant reduction of friction coefficient and thus of friction torque, in relation to not only unmodified polypropylene but also the examined polyamide and Teflon.